The Effect of Management Pressure, Locus of Control and Audit Disfunctional Behavior on Auditor Performance (Empirical Study of Public Accounting Firms in Medan City) - Dinda Audria; Reza Hanafi Lubis (International Journal of Economics (IJEC), 2022)
This study aims to analyze the effect of management pressure, locus of control and dysfunctional audit behavior on auditor performance. The research data is primary data by distributing questionnaires via google form to respondents. and processed using multiple linear regression analysis. The population and sample in this study amounted to 23 KAPs in Medan City but only 5 KAPs were accepted, so the sample used was 37 auditors. The results showed that management pressure, locus of control and dysfunctional audit behavior had an effect on auditor performance. Based on the conclusions above, the authors write some suggestions that are expected to be useful for 5 Public Accounting Firms in Medan City, namely for auditors it is expected to always teach and control Auditor dysfunctional behavior, so as to create good and quality Auditor Performance, for Public Accounting Firms are expected to provide good performance. good for clients by providing quality audit services and results, further researchers are expected to be able to add variables that affect Auditor Performance, because in this study only used variables Management pressure , Locus Of Control and Auditor Dysfunctional Behavior.